Production and characterization of conical shaped ultra-high temperature ceramics matrix composites by slip casting and pressure-less sintering - Matteo Mor; Simone Taraborelli; Diletta Sciti (Open Ceramics)
This study investigates the fabrication and characterization of cone shaped fibre reinforced ultra-high-temperature ceramic matrix composites (UHTCMCs) based on ZrB2, using slip casting and pressure-less sintering at 2100 °C in Ar. For the sake of comparison, the same process was used for production of bulk ZrB₂-based cones. The slip casting technique effectively ensured a homogeneous fibre distribution in the sample. The addition of fibres imparted a sufficient mechanical resistance to the green bodies and led to near no shrinkage during densification, achieving a lightweight conical structure with a density of 1 g/cm3. Despite the high content of porosity, the cones survived two consecutive oxidation tests at 1650 °C for 1 and 3 min. Overall, slip casting proved to be a viable method for producing UHTCMCs with complex shapes and oxidation resistance.